Pengaruh Flexible Working Arrangement, Work Life Balance, Terhadap Job Satisfaction yang Dimediasi oleh Work Engagement pada Karyawan Milenial PT Nagahama Mesin Balancing - Enjang Suherman; Flora Patricia Anggela; Salsa Padia Putri (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
The purpose of this study was to determine the effect of Flexible working arrangements and Work life balance on Job Satisfaction with Work engagement as a mediating variable. This research uses quantitative methods with the number of samples being employees of PT Nagahama Balancing Machine with a total of 100 respondents. This research is processed using SmartPLS 3 data processing software and data collection is done through Google forms. The results of this study indicate that the Flexible Working Arrangement (X1) variable has a positive effect on Job Satisfaction (Y) with a t statistic value of 16.082 and a significant value of 0.000. Work Life Balance (X2) has a positive effect on Job Satisfaction (Y) with a t statistic value of 7,123 and a significant value of 0.000. Work Engagement (Z) has a positive effect on Job Satisfaction (Y) with a t statistic value of 5.001 and a significant value of 0.000. Flexible Working Arrangement (X1) has a positive effect on Work Engagement (Z) with a t statistic value of 4.911 and a significant value of 0.000. Work Life Balance (X2) has a positive effect on Work Engagement (Z) with a t statistic value of 4.202 and a significant value of 0.000. Flexible Working Arrangement (X1) through Work Engagement (Z) as a mediating variable has a positive effect on Job Satisfaction (Y) with a t statistic value of 3.819 and a significant value of 0.000. Work Life Balance (X2) through Work Engagement (Z) as a mediating variable has a positive effect on Job Satisfaction (Y) with a t statistic value of 2.835 and a significant value of 0.000.